SkaSim – Skalierbare HPC‐Software für molekulare Simulationen in der chemischen Industrie. Issue 3 (1st February 2018) - Vrabec, Jadran; Bernreuther, Martin; Bungartz, Hans‐Joachim; Chen, Wei‐Lin; Cordes, Wilfried; Fingerhut, Robin; Glass, Colin W.; Gmehling, Jürgen; Hamburger, René; Heilig, Manfred; Heinen, Matthias; Horsch, Martin T.; et al.
Abstract: This article outlines advances in molecular modeling and simulation using massively parallel high‐performance computers (HPC). In the SkaSim project, partners from the HPC community collaborated with users from science and industry. The aim was to optimize the prediction of thermodynamic property data in terms of efficiency, quality and reliability using HPC methods. In this context, various topics were dealt with: atomistic simulation of homogeneous gas bubble formation, surface tension of classical fluids and ionic liquids, multicriteria optimization of molecular models, the development of the molecular simulation codes ls1 mardyn and ms2, atomistic simulation of gas separation processes, molecular membrane structure generators, transport resistors and the evaluation of predictive property data models based on specific mixture types.